MAPPING LITERARY MATERIAL IN THE INDONESIAN LANGUAGE AND LITERATURE TEXTBOOK IN KURIKULUM MERDEKA FOR HIGH SCHOOL LEVEL - Kharisma Endah Susanti; Arif Setyawan (SOSIOEDUKASI, 2026)
This study aims to map the literary material contained in the Smart and Intelligent Indonesian Language and Literature textbook for the Independent Curriculum (Kurikulum Merdeka) for high school. The study focuses on the form, type, and depth of the literary material presented in the textbook and its suitability to the learning outcomes of the Independent Curriculum. This study uses a qualitative descriptive method with content analysis techniques. Data include texts, learning activities, and literary project assignments contained in the textbook for grades X, XI, and XII. The results show that the literary material in the textbook covers various genres, including poetry, short stories, novels, drama, and literary reflective texts. The material is presented with a contextual and integrative approach that emphasizes appreciation, interpretation, and creative expression of students. However, there is an imbalance in the proportion between classical and modern literature, as well as limited exploration of regional literary works and digital contemporary literature. In conclusion, this textbook has implemented the spirit of the Independent Curriculum, which emphasizes experience-based literary learning and humanitarian values. However, it needs content enrichment and cross-cultural appreciation activities to make literature learning in high school more holistic and relevant to current developments.